Housing with support for older people: a mixed-methods systematic review protocol [version 1; peer review: 2 approved] - Camille Coyle; Sarah Buggy; Olivia Cagney; Louise Farragher; Caitriona Lee; Darren Patje; Jean Long (HRB Open Research, 2020)
Background: The implementation of housing with support is rapidly expanding, particularly as life expectancy is increasing throughout the world. This expansion is likely to intensify in the context of coronavirus disease 2019 (COVID-19), which has revealed the risks of relying primarily on nursing homes. This mixed-methods systematic review aims to: 1) explore older people’s perceptions and experiences of housing with support and 2) examine the impact of providing housing with support for older people. Methods: The databases Ovid Medline, Ovid Social Policy & Practice, EBSCO CINAHL, and EBSCO SOCIndex will be searched, and grey literature will also be identified. Quality assessment will be carried out using Joanna Briggs Institute’s Critical Appraisal Checklist for Qualitative Research as well as a tool from the National Institutes of Health for observational cohort studies. This review will employ convergent parallel design; as such, qualitative and quantitative findings will be synthesised separately in the initial stage of analysis. The results from the qualitative and quantitative syntheses will then be integrated in the final stage of the analysis. Conclusion: This systematic review will synthesise the evidence regarding older people’s perceptions and experiences of housing with support and the impact of providing housing with support for older people on their quality of life.